Oral health related quality of life among adults reffered to dental clinic of Babol Faculty of Dentistry in 2009-2011 - Effat Khodadadi; Mina Motallebnejad; Mehnoosh Alizadeh (Caspian journal of dental research, 2013)
Introduction: The quality of life is defined as the individual's sense of well-being and their satisfaction with daily work as influenced by dental and oral conditions. Oral diseases are very common and have impacts on the different aspects of individual's life and can change their social performances roles, in other words, they can change the quality of life. The aim of this study was to evaluae the impact of oral problems on quality of life in adults who referred to Babol Faculty of Dentistry during 2009-2011. Methods: This cross-sectional study was performed using a non-randomized sampling method. In this study, 500 patients who referred to Babol Faculty of Dentistry age 20-50 years were selected. Then all the questions in OIDP (Oral Impact on Daily Performance) questionnaire which were translated into persian from english were asked and completed. These questions are valuable and reliable for Iranians based on the previous studies. Finally, the data were analyzed by SPSS statistical software. Results: According to this study, oral problems have effected on (80.6%) of the patients’ quality of life. Gender, occupation, level of education and general health have impacted on OIDP score changes. There were significant differences in gender, occupation and level of education. In this study, the general and oral health conditions scores showed a significant association with OIDP score. Most of the patients’ complaint was about eating (64.4%), but going outside and shopping were the least (10%). Conclusions: According to the results of this study, tooth pain was the most oral and dental problem and tooth shape and size were the least effective on the oral health related quality of life. This shows that the most needed treatment are tooth restoration، root canal therapy and surgical treatment for pain relief.